Emotional Labor Dilemmas and Coping Strategies of Novice Teachers in the Guangdong-Hong Kong-Macao Greater Bay Area Universities - Guo, Qin (Transactions on Social Science, Education and Humanities Research, 2023)
With the rapid development and economic integration of the Guangdong-Hong Kong-Macao Greater Bay Area, applied undergraduate education plays an important role in the universities in this region. However, novice teachers often face dilemmas in emotional labor and need to cope with various pressures and challenges. This study aims to explore the emotional labor dilemmas faced by novice teachers in applied undergraduate education in the Guangdong-Hong Kong-Macao Greater Bay Area and propose corresponding coping strategies. Through data collection methods including questionnaires and in-depth interviews with novice teachers in applied undergraduate education in selected universities in the Greater Bay Area, this study analyzes the issues they encounter in emotional labor. It explores the coping strategies that teachers in the Guangdong-Hong Kong-Macao Greater Bay Area may adopt to deal with emotional labor dilemmas.